Semitendinosus muscle morphology in relation to surface electrode placement in anterior cruciate ligament reconstructed and contralateral legs - Kositsky, Adam; Barrett, Rod S.; du Moulin, William; Diamond, Laura E.; Saxby, David J. (Frontiers in Sports and Active Living, 2022)
The semitendinosus tendon is commonly harvested as graft tissue for anterior cruciate ligament reconstruction (ACLR). Although the semitendinosus tendon can regenerate following harvesting, ACLR results in substantial reductions in semitendinosus muscle size and length, potentially complicating electrode placement for electromyography. The purpose of this study was to assess whether the most commonly used electrode placement [recommended by the “Surface Electromyography for Non-Invasive Assessment of Muscles” (SENIAM) project] is appropriate for measuring semitendinosus electromyograms after ACLR. In nine participants (unilateral ACLR with a semitendinosus graft), B-mode ultrasonography was used to bilaterally determine (i) the semitendinosus muscle-tendon junction position and the state of tendon regeneration (latter for the ACLR leg only) and (ii) the anatomical cross-sectional area (ACSA) of the semitendinosus muscle at the SENIAM-recommended electrode placement site at rest and during isometric maximal voluntary contraction (MVC) at two knee joint angles. Depending on the contraction state and joint angle, the semitendinosus muscle had retracted past the recommended placement site in 33–78% of ACLR legs, but not in any contralateral legs. The ACSA of semitendinosus was smaller both at rest and MVC in the ACLR compared to contralateral leg. The ACSA for both legs decreased at MVC compared to rest and at deep compared to shallow knee flexion angles, likely due to sliding of the muscle under the skin. These results suggest SENIAM guidelines are likely unsuitable for recording surface electromyograms from the semitendinosus muscle after tendon harvesting for ACLR as the muscle of interest may not be within the electrode detection volume.